If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(2/3)*(6-8*x) = -2 // + 2
(2/3)*(6-8*x)+2 = 0
2/3*(6-8*x)+2 = 0
2/3*(6-8*x)+2 = 0
6-16/3*x = 0
6-16/3*x = 0
6-16/3*x = 0 // - 6
-16/3*x = -6 // : -16/3
x = -6/(-16/3)
x = 9/8
x = 9/8
| 2(x-2)-1=-9 | | 2-4(8-8x)=0 | | (9xn)+6=0 | | 26x^4y^7-34x^3y^4+12x^8y=0 | | 4-8(9x+5)=2 | | 3/2(-2x+6)=-6 | | -2.8*-2.8-2.6y=-9.1 | | 3+7/c=0 | | x+(4x-30)=x+(3x+10) | | 15-3y=6 | | -3x+9=-6x-5 | | -2.6*7.8+1.2y=7.8 | | -14x+47=-7x+5-4x | | -2.6*-2.6+1.2y=7.8 | | (y+5)+1=4y | | y+5+1=4y | | 4.2*-9.1+2.5y=-9.1 | | (4/12)+(2/21) | | (x-4)+5=0 | | x+39=2x | | 4*-8.5+3.7y=-8.5 | | 6x-5=3x-3 | | 4x+3.7(4)=-8.5 | | 6x+12+15-10x=7-2x | | 2x+5=25+x | | 10x-6=12x-20 | | 2x+6=3x-8 | | x-4+5=0 | | 3(x+5)-8whenx=9 | | x+8=x-12 | | 3(x+5)-8x=9 | | -27=12x+27 |